Colorectal Surgery in Cirrhotic Patients - Jacqueline Paolino; Randolph M. Steinhagen (The Scientific World Journal)
Patients with cirrhosis have a greater risk of morbidity and mortality following colorectal surgery. Therefore, preoperative medical optimization and risk assessment using criteria such as the MELD score are vital in preventing complications. Some risk factors include age, urgency of surgery, and ASA score. Postoperative morbidity and mortality are related to portal hypertension, ascites, infection, and anastomotic and stomal complications. This review highlights the assessment of risk and perioperative management of cirrhotic patients undergoing colorectal surgery.